2016
DOI: 10.1097/md.0000000000004911
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial hypertension in idiopathic inflammatory myopathies

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Autoimmune features in patients with ILD are important features in the natural history of the disease, and studies have reported that patients with inflammatory myopathies associated ILD have worse morbidity and higher mortality than patients without [ 47 ]. A retrospective cohort suggested that poorer pulmonary function test is more common in more severe PM/DM [ 48 ] and data from a nationwide prospective Pulmonary Hypertension Registry in France indicated a very possible association between inflammatory myopathies and pulmonary arterial hypertension [ 49 ]. This may, in part, explain the associations between high DRR with disease severity and mortality in the 1-year follow-up in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune features in patients with ILD are important features in the natural history of the disease, and studies have reported that patients with inflammatory myopathies associated ILD have worse morbidity and higher mortality than patients without [ 47 ]. A retrospective cohort suggested that poorer pulmonary function test is more common in more severe PM/DM [ 48 ] and data from a nationwide prospective Pulmonary Hypertension Registry in France indicated a very possible association between inflammatory myopathies and pulmonary arterial hypertension [ 49 ]. This may, in part, explain the associations between high DRR with disease severity and mortality in the 1-year follow-up in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Data on confirmed cases of CTEPH for the KB hospital were available from a prospective database set up for observational research ( tableau de bord du centre de référence hypertension artérielle pulmonaire et requêtes patients ). Confirmed cases from the second centre (LP) were extracted from the French PH registry, which was opened in 2002, and planned to enrol all consecutive patients aged ≥18 years with PH [1416].…”
Section: Methodsmentioning
confidence: 99%
“…A majority of myositis-associated lung involvement manifests as ILD. Unlike in SSc, isolated PAH is rare in myositis [ 67 ]. ILD manifests early in the course of myositis, often found at the time of diagnosis [ 4 , 68 , 69 ].…”
Section: Interstitial Lung Disease (Ild)mentioning
confidence: 99%